PROFIL PASIEN KERATOSIS SEBOROIK DI POLIKLINIK KULIT DAN KELAMIN RSUP DR. M. DJAMIL PADANG TAHUN 2016-2019 - Tripuspita PAF; Anandia Putriyuni; Jenny Tri Yuspita Sari; Jon Hadi; Anggun Rihani (Nusantara Hasana Journal, 2023)
Seborrheic keratosis is a benign skin tumor that originates from the proliferation of the epidermis and the buildup of keratin on the surface of the skin. Factors that cause include age, sun exposure, and infection. Various indications for removal of the lesion include signs of malignancy, irritation with inflammation and especially for cosmetic purposes in patients with multiple lesions. KS cases are increasing overseas and quite high reported in several hospitals in Indonesia. This research to know and identify the profile of seboroik keratosis patients at Dr.M. Djamil Padang Hospital in 2016-2019. This type of research is descriptive. With cross-sectional study design. The affordable population in this study was patients diagnosed with seboroik keratosis who were treated at Dr.M. Djamil Padang Hospital in 2016-2019 with 80 samples in total sampling. Research variables consist of age, gender, main complaint, location of lesions. The most research found were ages 41-65 years, namely 37 people (46.3%), female sex of 54 people (67.5%), the main complaint of lesions increased by 22 people (38.8), 2 or more locations lesions were 33 people (41.2%) and surgical therapy of 43 people (53.7%). Seboroik keratosis patients at Dr.M. Djamil Padang Hospital in 2016-2019 most age 41-65 years, female sex, main complaints of increased lesions, 2 or more locations lesions and surgical therapy.